University scientists’ willingness to participate in public engagement: A concept explication - Becca Beets; Mikhaila N. Calice; Lindsey Middleton; Dominique Brossard; Dietram A. Scheufele; Luye Bao; Todd P. Newman; Jo Handelsman (PLoS ONE, 2025)
Public engagement is increasingly recognized as a critical responsibility of the scientific community. Scientists in academic settings are well positioned to lead these efforts, but they are not always willing or able to participate in engagement. Public engagement can encompass a range of activities that may require different resources and skills, and which may have different outcomes for both scientists and non-scientists. Therefore, understanding which activities scientists are willing to participate in is critical for supporting their engagement efforts at the institutional level. Using survey data from a case study of science faculty at a large land-grant university in the United States, we conduct a systematic concept explication to better understand the dimensions of public engagement activities that scientists are willing to participate in. Based on thirteen different activities, we define and analyze the reliability of five dimensions of engagement: public scholarship, educational activities, direct engagement with public audiences, stakeholder-focused collaboration, and industry engagement. We also examine the validity of these five dimensions and how factors including institutional culture and norms, professional status, and attitudes towards engagement relate to scientists’ willingness to participate in engagement. Our results provide a robust categorization of willingness to engage as a blueprint for future research in this space.